Public administration and politics: correlation of theoretical concepts in historical retrospect - Grybko, Olha (Pressing Problems of Public Administration, 2022)
The article analyzes the classification of the relationship between politics and administration, it was found that four models are distinguished according to the degree of interrelationship: classical, bureaucratic, deliberative, and hybrid. The formation and characteristic features of each model are considered. It was singled out a number of advantages of the hybrid model and given four main reasons that recommend its use: 1) provides an innovative (non-rationalist) view of the political process; 2) integrates policy and administration; 3) is sensitive to the complex nature of public policy; 4) it has the potential to deepen the democratic process.In modern socio-economic conditions, the Ukrainian system of public administration has not yet found an optimal relationship between politics and administration, there is no clear separation of administrative and political functions. The reality of public administration shows that Ukraine lacks professional administrators-managers, free from the “pressure” of politics, as well as politicians who understand administrative mechanisms. However, the science of public administration was conceived as a technical way of solving social problems, which allows people to avoid the pitfalls of politics. It can be said that society would have better life if the collective decision-making process was devoid of political mediation and instead based solely on scientific approach.Although even in this case, it is worth remembering that public administration, which is guided by the instrumental type of rationality, does not allow civil society (which is based on the communicative type of rationality) to have a significant impact on administrative activities.Therefore, in our opinion, the best way to combine such similar and at the same time different phenomena as politics and administration is the method proposed by the hybrid model, because it defines: a) that public administration performs both administrative and political tasks; b) the political process as a continuous dispute that is never resolved forever, the hybrid model is adapted to the increasingly complex conditions of policy formation.After all, the hybrid model notes the coexistence of several views; it allows political subjects to express their disagreement through political centers. By identifying conflict in the political process, the hybrid model promotes the development of democratic practices and institutions. Dissent, rather than binding consensus, is indispensable for revitalizing democratic processes and eliminating the “democratic deficits” that pervade modern societies.